TABOOS SPOKEN BY THE CHARACTERS IN A SPONGEBOB MOVIE: SPONGE ON THE RUN PLAYING IN MOVIES IN 2020 - Taruna Bachtera Bachtiar; Liliek Soepriatmadji (Universitas Stikubank (UNISBANK) Semarang, 2022)
This study aimed to investigate if there are types and function of taboo words in a SpongeBob Movie: Sponge on the Run movie. It was taken from the dialogues in the movie that shows taboo. This study used descriptive qualitative method. The researcher analyze data using two theories, they are Battistella and Wardhaugh theories. The study answered two questions related to statement of the problems. First is what type of taboos are produced and the second is what are the functions that those taboo words by the characters in whole dialogue. The results indicated that: 1) three types appears: epithet, profanity, and vulgarity. Epithet becomes the most type used in the movie because it is used as slurs to the listeners. Besides, vulgarity becomes the least type of it. 2) Several functions appears too. First is to get attention, second is insult to other, and least is provoke. Insulting becomes the most dominant function used because they like to disdain or offend other characters pride. Meanwhile, taboo words used to provoke appears as the least function in the movie. The result of this research can be used as a warning for ourselves (especially Indonesian parents) if taboos can appears in serial cartoon movie. Keywords: Taboo words, types, function, SpongeBob Movie.